Prenatal diagnosis of primary congenital glaucoma and histopathological features in a fetal globe with cytochrome p4501B1 mutations. Issue 2 (March 2022) - Rezaei Kanavi, Mozhgan; Yazdani, Shahin; Elahi, Elahe; Mirrahimi, Mehraban; Hajizadeh, Maryam; Khodaverdi, Sepideh; Suri, Fatemeh
Background/Objectives: This study aims to report the developmental and histopathological features of ocular tissues from an electively aborted human fetus with mutations in cytochrome p4501B1, and thus predisposed to primary congenital glaucoma in comparison to an age-matched healthy fetal globe. Subjects/Methods: Both eyes of two 17-week gestational aged fetuses, the first with CYP1B1 mutations and the second as healthy control fetus, were studied. Hematoxylin and eosin, Periodic acid–Schiff, Gomori's trichrome, and Verhoeff–Van Gieson staining protocols in addition to immunohistochemistry staining using anti-cytochrome p4501B1, anti-fibrillin-1, and anti-4-hydroxy-2-nonenal antibodies, as primary antibodies, were performed to assess the effect of the mutations on tissue development, cytochrome p4501B1 protein expression, extracellular matrix structure, and oxidative stress in the developing fetus eye. Quantitative analyses were performed using ImageJ software. Student's t -test was used for statistical analysis and P -values <0.05 were considered as significant. Results: Delayed development in ocular tissues, decreased expression of cytochrome p4501B1 protein, irregular extracellular matrix structure, and increased oxidative stress biomarker were evident in the ocular tissues of the fetus with cytochrome p4501B1 mutations as compared to a normal globe from an age-matched fetus. Conclusion: To the best of our knowledge, this is the first report of prenatal diagnosis of primary congenital glaucoma. We also describe histopathological changes in the primary congenital glaucoma-affected globes revealing the effect of cytochrome p4501B1 deficiency on ocular tissues during early fetal development contributing to the glaucoma phenotype.